Komunikasi Interpersonal Pimpinan Dalam Meningkatkan Kinerja Karyawan PT Bank SUMUT Syariah KCP Stabat - Bambang Irwansyah; Yaumul Khair Afif (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to determine leadership interpersonal communication in improving employee performance at the Bank Sumut Syariah Office KCP Stabat. This type of research is qualitative research. Methods of collecting data by means of observation, interviews and documentation. Data analysis techniques used with data obtained through the process of data reduction, data presentation and conclusion drawing or verification. The results of this study show that the implementation of interpersonal communication at PT Bank Sumut Syariah KCP Stabat occurs directly (primary) and indirectly (secondary), between employees and leaders apply the law of positive attitudes in interpersonal communication including: openness, empathy, supportive attitude, positive attitude, equality. The importance of leadership interpersonal communication in improving employee performance, part of the interpersonal communication of leaders is able to have an impact on employee work motivation, because it is able to meet the needs of security, social needs, the need for appreciation, the need for self-actualization, but there are some needs that cannot be influenced by their existence. interpersonal communication, namely physiological needs and self-transcendence. Supporting factors for interpersonal communication include the internal factors of the personal communicator, speaking ethics with courtesy, realistic, time, place and openness. While the inhibiting factors for interpersonal communication of leaders in increasing employee work motivation include the intent of the communicator not being accepted by the communicant, presumptions between the communicator and the communicant, the communicator not being interested in communication.